EKSPLORASI KARAKTER SEKUNDER UNTUK SELEKSI TIDAK LANGSUNG PADA JAGUNG DI KONDISI KEKERINGAN - Slamet Bambang Priyanto; Moch. Arif Subechan (Politeknik Negeri Lampung., 2023)
Yield maize direct selection at drought conditions sometimes is inefficient. Indirect selection through secondary characters can increase selection efficiency. This study aims to obtain secondary characters that can be used for indirect selection. This research was conducted at IP2TP Bajeng, Indonesia Cereal Research Institute, Gowa Regency, South Sulawesi Province from July to November 2020. The research was arranged in a randomized Alpha Lattice group design with three replications. The genotypes used were 36 hybrid maize candidates and four comparison varieties. Characters that have high diversity are determined by a loading factor value of more than 0.7. The correlation between secondary characters and yield was using Pearson correlation and heritability ​​are derived from the analysis of variance. The results showed that the characters of day to anthesis, day to silk, number of harvested ears and ear diameter were secondary characters that could be used as the indirect selection of maize in drought conditions. drought;; indirect selection, maize; secondary characters